Tao e umu ke moho. Receptive Bilingualism of Vagahau Niue: A Case Study of Lived Experiences from First-generation New Zealand-born Niue Living on a Distant Shore, Aotearoa. - Tukimata, Nogiata (Auckland University of Technology, 2024)
Receptive bilingualism, a relatively modern concept of the overarching topic of bilingualism, is defined by scholars as having a comprehension of a language but the production of it not (Romaine, 1989; Fishman, 1991; Rehbein et al., 2012; Radley et al., 2021). The case study of the Niue community, and more importantly, first-generation New Zealand-born Niue, helps to formulate and raise awareness of the significance of receptive bilingualism as a changing factor that impacts the revitalisation of minority and migrant languages today. Language revitalisation and maintenance contribute significantly to vagahau Niue (Niue language) in its ability to communicate and understand the language that encourages the deepening of the vahaloto (space, between time or space) (Vilitama, 2015) through exploration and celebration, and where cultural identity can be connected. As language maintenance and revitalisation are associated with the holistic well-being of native speakers and the communities in which they are immersed, protecting the continued vitality of vagahau Niue is important for the renewal and regeneration of cultural practices, traditions and behaviors. As this study is the first for receptive bilingualism of vagahau Niue, it signifies a critical point in time for how vagahau Niue is rapidly declining in a changing New Zealand society. This study, located in an Indigenous (Niue) framework, combines a Niue-centred methodology with a Pacific paradigm through the Niue concept of tutala (to converse) – in which 15 voices of lived experiences from the views of first-generation New Zealand-born Niue living in Aotearoa are seen as a cultural marker of identity and as part of the revitalisation process where maintaining vagahau Niue is critical for future use and future generations. The Niue model of the ‘Umu’ (earth oven) is used as an Indigenous symbolic reference for the research process and with the tutala interviews, as it lies at the heart of communal life and for its capacity to exercise a representative metaphorical role. The ‘Umu’ as a symbol is described by Vilitama (2015) as “being laden with rich themes” (p.212) that will help to analyse the data of the research through thematic analysis of both quantitative and qualitative datasets. Research findings revealed that receptive bilingualism impacted the participants through Fishman’s (1972) domains of language use, in which the findings established that the participants viewed their family structure as the fundamental domain of where their understanding of vagahau Niue came from and signified the role of their grandparents and parents as being critical to their upbringing and knowledge with the language. In turn, the participants determined that other domains of language use assisted with their receptive skills, such as the church, classroom setting, and the influence of digital technology. The overall empirical findings for this research contribute to the limited scope of literature about receptive bilingualism and identify new tensions in receptive bilingualism among minority languages that are yet to be discussed in the literature, as well as how language maintenance pertains to the identities of first-generation New Zealand-born Niue, are impacted by receptive bilingualism – a way forward for vagahau Niue language revitalisation for the generations of Niue in the present, and subsequent Niue generations in the future.